The changing electoral landscape of Spain (2015-2019) - A. A. Kurakina-Damir (Ибероамериканские тетради, 2021)
In the middle of the second decade of the 21st century there has begun a process of reorganization of Spanish electoral landscape. The Congress of Deputies (lower, and the key chamber of the Spanish Parliament) in its 2019 iteration is not much like the Congress of 2000-2011. The list of parties does not include Unión, Progreso y Democracia (UРyD) and Izquierda Unida (IU), which were predicted to grow significantly due to the decline in competitiveness of the leading parties, and were replaced by new members – Podemos, Ciudadanos, Más País, Teruel Existe. The Catalan parties, being the representatives of the most politically intense region of Spain, were also significantly altered and consequently strengthened their positions. A number of autonomous regions changed their ‘party affiliations’, and an atmosphere of uncertainty reigned in sparsely populated provinces. The author discusses main reference points for the political process of the country which significantly changed the balance of power, as well as the difficulties that political actors faced in the process of reaching or not reaching sought compromises. Over the past 4 years voters have been forced to return to polling stations twice to elect the national Parliament. Evidently, the Cabinet must urgently reform the system of government formation in order to avoid similar problems in the future.